SUBSITUSI PENAMBAHAN TEPUNG IKAN GABUS TERHADAP COOKIES TEPUNG SAGU SEBAGAI ALTERNATIF MAKANAN SELINGAN IBU HAMIL - Ridha Daniar; Yulia Mandasari (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2023)
This research is motivated by the absence of a pastry industry that makes snakehead fish flour for processing cookies, especially by making snakehead fish in the form of flour. This is a creative idea from the pastry industry. Therefore the authors want to do research on snakehead fish flour in making cookies, so that pregnant women can be creative in processing snack foods. The research method used is the experimental method. Data collection techniques used were documentation studies, questionnaires and literature studies. This research was assessed by panelists about snakehead fish flour cookies. The results of this study indicate that the quality of the aroma of snakehead fish flour cookies, the panelists smelled more of the snakehead fish aroma in the R2 treatment. The color quality of snakehead fish flour cookies, the panelists saw more brown color cookies in both treatments. The quality of the shape of the snakehead fish flour cookies, the panelists saw more of the rounded shape of the cookies in the R1 treatment. The quality of the shape of the snakehead fish flour cookies, the panelists saw more of the rounded shape of the cookies in the R1 treatment. The texture quality of the snakehead fish flour cookies, the panelists saw the texture of the cookies with a crunchy texture in the R1 treatment. The quality of the taste of snakehead fish flour cookies, the panelists felt the taste of snakehead fish flour was more pronounced in the R2 treatment. The quality of the sweet taste of snakehead fish flour cookies, the panelists felt the taste of cookies more in the R1 treatment.